Sonication of revised hip and knee prostheses detects occult infections, improves clinical outcomes and prevents re - revisions. A case series study. Issue 3 (September 2022) - Hadjimichael, Argyris C.; Foukas, Athanasios F.; Kaspiris, Angelos; Vasileiou, Dimitris; Kamariotis, Spyros; Stylianakis, Antonios; Vasiliadis, Elias S.; Savvidou, Olga D.; Antonopoulos, Athanasios
Summary: Introduction: Periprosthetic joint infection (PJI) is a devastating complication occurring in 1–2% of primary and up to 10% of revised total hip and knee arthroplasties (THA and TKA) impairing patient's quality of life. Occult infections are underdiagnosed, sub-treated and sub-clinically experienced by patients. This study aimed to correlate patients' clinical outcomes with early antibiotic treatment based on use or non-use of a sonication technique on explanted prostheses. Methods: 33 patients with revised THA or TKA were retrospectively evaluated. Clinical outcomes were assessed via Oxford hip or knee scores, and correlated with administration or not of antibiotic treatment based on sonication results. Results: According to laboratory findings the patients were divided in the following three groups: 1. Septic loosening (conventional cultures and/or sonication positive), 2. Aseptic loosening (conventional cultures and sonication negative) and 3. Occult loosening (conventional cultures negative, sonication not performed). The average Oxford score was poor (27.9/60) for the septic, excellent (43.8/60) for the aseptic and intermediate (37.7/60) for the occult group. Additionally, conventional cultures were negative, but sonication-positive, in 6 individuals with patient-related risk factors (male gender, BMI > 30 kg/m 2, diabetes, hypertension, steroids and rheumatoid arthritis). Conclusions: Sonication represents a valuable diagnostic technique to guide administration of effective antibiotic treatment for patients, especially for detection of persistent post-revision occult infections. We recommend the systematic investigation of revised prostheses with a sonication technique, but especially in cases with risk factors for infection who it is suspected may have occult loosening.